Pengaruh Fluktuasi Harga Emas, Promosi, Dan Resiko Investasi Terhadap Minat Masyarakat Pada Produk Tabungan Emas - Khurotul Fadilah; Amma Fazizah (FEB Universitas Maritim Semarang, 2023)
The purpose of this study was to determine the effect of gold price fluctuations, promotions, and manual gold investment risks on public interest in gold savings products at PT Pegadaian UPC Purwosari (Study on Communities in Purwosari District). This type of research is a quantitative research. The population in this study is the community in Purwosari District. The sample in this study amounted to 400 respondents and the sampling technique used purposive sampling with several criteria for respondents who lived in Purwosari District, were not yet customers and did not have a gold savings product at PT Pegadaian UPC Purwosari, and were over 17 years old. Source of data in this study is sourced from primary data. Data collection techniques used by distributing questionnaires. The analytical tool used is multiple linear regression analysis. The results of this study indicate that fluctuations in the price of gold have a positive but not significant effect on people's interest in gold savings products, promotions have a positive but not significant effect on people's interest in gold savings products, and investment risk has a positive and significant effect on people's interest in gold savings products. Fluctuations in gold prices, promotions, and investment risks affect people's interest in gold savings products.